PENGARUH PERILAKU PEMIMPIN TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN MIOMAFO TIMUR - Anita Lassa (Universitas Nusa Cendana, 2017)
This research aims to know the influence of the Task-Oriented Leader Behavior and Relationship-OrientedLeader Behavior, simultaneously and partially towards Employees Performance at Kantor KecamatanMiomafo Timur. The type of research is survey research with the quantitative approach. Method of analysisis the multiple linear regression. The research found that the independent variables Task-Oriented LeaderBehavior (X1) and Relationships Oriented Leader Behavior (X2) simultaneously influenced to EmployeesPerformance with a value of Fcount (90.309) > Ftable (2.33). Task-Oriented Leader Behavior (X1) andRelationships-Oriented Leader Behavior (X2) influenced to Employees Performance partially with a valueof tcount > ttable : 17.760 and 11.457 respectively > 2, 119Keywords : Employees Performance, Task-Oriented Leader Behavior and Relationships-Oriented LeaderBehavior